Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
42 . x -1 = 7.32
16 . x - 1= 7.9
16 . x -1 = 63
16 . x = 63 + 1
16 . x = 64
x = 64 : 16
x = 4
42.x-1=7.32
16.x-1=7.9
16.x-1=63
16.x=63+1
16.x=64
x=64:16
x=4
b.\(3^{x+2}\)+4.\(3^{x+1}\)=7.\(3^6\)
\(3^2\).\(3^x\)+4.3.\(3^x\)=7.\(3^6\)
9.\(3^x\)+12.\(3^x\)=7.\(3^6\)
\(3^x\)(9+12)=7.\(3^6\)
\(3^x\).21=7.\(3^6\)
\(3^x\)=7.\(3^6\):21
\(3^x\)=\(3^6\):3
\(3^x\)=\(3^5\)
x=5
a) \(\frac{5}{6}+\frac{7}{12}-\frac{2}{3}\)=\(\frac{10}{12}+\frac{7}{12}-\frac{8}{12}\)=\(\frac{9}{12}=\frac{3}{4}\)
b) \(\frac{3}{4}-1\frac{1}{2}+50\%:\frac{5}{12}\)=\(\frac{3}{4}-\frac{3}{2}+\frac{1}{2}:\frac{5}{12}\)=\(\frac{3}{4}-\frac{3}{2}+\frac{6}{5}\)=\(\frac{30}{40}-\frac{60}{40}+\frac{48}{40}\)= \(\frac{18}{40}\)=\(\frac{9}{20}\)
c)ghi lại đề hộ mk, mk ko rõ
1. (-6 - 2).(-6 + 2)=(-6 - 2)=-8;(-6 + 2)=-8
=>-8+-8=-16
2. (7.3-3) : (-6)=(7.3-3)=18 : (-6)=-3
3. (-5+9).(-4)=(-5+9)=4.(-4)=-16
4. 72:(-6.2+4)=72 : -8=-9
\(4^2x-1=7.3^2\)
<=>\(16x-1=7.9\)
<=>\(16x-1=63\)
<=>\(16x=64\)
<=>\(x=4\)
42 . x - 1 = 7 . 32
42 . x - 1 = 7 . 9
42 . x - 1 = 63
16 . x = 63 + 1
16 . x = 64
x = 64 : 16
x = 4
Hoc tot!!!